Development of Teaching Materials on Geometry Materials to Develop Students' Critical Thinking Skills According to the Criteria for Critical Thinking 4C's - Fitri Umardiyah; Zaidatur Rohmah (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to determine the development of students' critical thinking skills through LKS teaching materials on flat plane geometry for class VII SMP/MTs are valid and practical. This research is a development research using the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). The analysis technique of this study uses validity test in the form of score scores from material experts and the value of the teacher's response to LKS teaching materials which is the value of the questionnaire. Practicality test in the form of responses from students and criticism or suggestions from validators. The results of this study produce a product in the form of LKS teaching materials. Product eligibility obtained based on the results of the validation test and practicality test. Assessment by material experts gets a score by 83% with a very valid classification or very feasible to use. Response questionnaire results the teacher got a score of 87% with a very valid classification or very feasible to use. The result of the student response questionnaire got a score of 87% with a very practical classification. Based on these results it can be concluded that the LKS teaching materials are very feasible to use.